Contractile reserve and cardiopulmonary exercise parameters in patients with dilated cardiomyopathy, the two dimensions of exercise testing. Issue 8 (6th July 2017) - Moneghetti, Kegan J.; Kobayashi, Yukari; Christle, Jeffrey W.; Ariyama, Miyuki; Vrtovec, Bojan; Kouznetsova, Tatiana; Wilson, Andrew; Ashley, Euan; Wheeler, Matthew T.; Myers, Johnathan; Haddad, Francois
Abstract : Background: Left ventricular (LV) contractile reserve assessed using imaging and cardiopulmonary exercise testing (CPX) has been shown to predict outcome in patients with dilated cardiomyopathy (DCM). Few clinical studies have, however, analyzed the relationship between them. Methods: A cohort of 75 ambulatory patients with DCM underwent stress treadmill echocardiography with CPX. LV contractile reserve was calculated as absolute change (ΔLVEF=LVEFpeak −LVEFrest ) and percent change (%LVEF=[(LVEFpeak −LVEFrest )/LVEFpeak) ]×100) in LVEF, circumferential and longitudinal strain (LS). Exercise capacity was measured as peak oxygen uptake (peak VO2 ) and ventilatory efficiency as the slope of minute ventilation to CO2 production (VE/VCO2 slope). Values of contractile reserve were compared to matched controls. We also explored which metric of ventricular response (absolute or percent change) was less dependent on baseline LV function. Results: Patients with DCM had a mean age, rest and peak LVEF of 44±10 years, 42±10% and 50±12%, respectively. Among parameters of contractile reserve, peak cardiac output was the strongest parameter associated with peak VO2 ( r =.63, P <.001). Along with age, sex, and BMI, it explained more than 70% of the variance in peak VO2 . In contrast, LVEF and LS were only weakly related to peak VO2 . With regard to ventilatory efficiency, the strongest parameter that emerged was right atrial volume index ( r =.36, P <.001). Percent change in LVEF was more independent of baseline function than absolute change. Conclusion: Echocardiographic contractile reserve and CPX provide complementary information. Percent change in contractile reserve was most independent of baseline function, therefore may be preferred when analyzing the ventricular response to exercise.